How populists fuel polarization and fail their response to COVID-19: An empirical analysis - Naushirvanov, Timur; Rosenberg, Dina; Sawyer, Patrick; Seyis, Didem (Frontiers in Political Science, 2022)
How well have populist leaders responded to the COVID-19 pandemic? There is a growing literature dedicated to populism and health outcomes. However, the ongoing pandemic provides us with a unique opportunity to study whether populist leaders fared better or worse than their non-populist counterparts by using a much larger sample size. While there has been a fruitful debate over whether populism is responsible for worse health outcomes, much of the focus has centered around the overall effect of having populist parties in power, without testing for different explanatory mechanisms. We argue that populist leaders fuel mass political polarization, which increases the overall level of hostility among the population and reduces their willingness to comply with anti-COVID measures and, more generally, contribute to public good. We test this theory using the expert-coded V-Party Dataset which contains variables for the ideological characteristics for parties around the world, as well as weekly excess mortality from the World Mortality Dataset. In addition to the OLS regression analysis, we employ a causal mediation framework to account for the order of succession of populism and political polarization. Our empirical results corroborate our main hypothesis that populism fuels political polarization, which is, in turn, associated with higher excess mortality during the ongoing pandemic. Our results are robust to alternative model specifications.